Tracing charge trajectories: a study of the influence of race in charge changes at case screening, arraignment, and disposition - Kutateladze, Besiki (Criminology, 2018)
Although social scientists and legal scholars have made valuable headway in identifying and explaining the relationships between myriad demographic, social, and legal factors and case outcomes, a sizable gap in understanding remains with respect to how cases evolve across decision points and how charges change for different racial and ethnic groups at individual decision points and cumulatively. This gap is partially addressed in this study through the examination of charge decreases, increases, and no change at three essential decision points—case screening for prosecution, arraignment, and final disposition. The results show that, overall, screening and disposition were much more dynamic decision points than was arraignment and that one third of cases experienced a charge decrease at some point. Even though racial differences in charge reductions at case screening were not large, at arraignment and disposition, as well as cumulatively, Black and Latino defendants were less likely than White defendants to have charges decreased. Conversely, Asian defendants experienced even more favorable outcomes than White defendants as they were more likely to have charges reduced and less likely to experience an increase. These findings are framed in the context of focal concerns, cumulative disadvantage, and “charge reasonableness” arguments.